Greenland, Boyd's ship, Veslekari at Ice Fjord, Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig 145 - The Veslekari at Renbukten, Ice Fiord. July 29, 1931. (X). (Caption taken Boyd, L. A. (1935). The Fiord Region of East Greenland (pp. 109). New York: American Geographical Society.) Veslekari (at Renbukten Ice Fiord, July 29, 1931), Fiord Region of East Grennland, p. 109 Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society